Creation of Islamic Branding Strategy in Digital Marketing: A Study on “Umair” The Product Line of Trisna Group's Subsidiaries - Dewani, Shinta Laura; Desy Putri Purnamasari; A. Anas Haikal; Gallant Yosava Swatantra (Al Tijarah, 2024)
Islamic branding, as a concept that integrates Islamic principles into brand marketing strategies, is not only an essential focus for companies that uphold religious values as their core identity but also serves as a marketing tool, particularly in digital marketing, targeting the Muslim market in Indonesia. This research aims to explore the implementation of Islamic branding in the digital marketing of product from Trisna Group Kediri's subsidiaries and to analyze the challenges and their solutions. The study employs a qualitative case study approach and triangulates data sources through observation, interviews, and documentation. The data collected will be reduced by summarizing, selecting key points, and focusing on significant aspects. The findings are then presented for better understanding and conclusions. The results indicate that product from Trisna Group Kediri’s subsidiaries “Umair” perfume has adopted Islamic branding in their digital marketing strategies, such as creating an Islamic-themed logo for Umair, the halal labeling process for Umair perfume, presenting Islamic content in Umair's digital marketing, endorsing Islamic influencers as Key Opinion Leaders (KOL) for digital promotion, and actively participating in various Muslim or halal fairs in Indonesia. Challenges identified include the frequency of digital content uploads and the website design resembling a landing page. Solutions to these issues involve brainstorming content ideas and benchmarking against similar companies, creating interactive content, scheduling posts automatically, and designing a more engaging and comprehensive website. Overall, the application of Islamic branding in digital marketing effectively optimizes the company’s efforts to attract the Muslim community market in Indonesia, and even other countries.